International development of transport enterprises in Ukraine during the war - Kersys, Robertas; Kobieliev, V. M. (Національний технічний університет "Харківський політехнічний інститут", 2025)
Transport enterprises in Ukraine faced many challenges during the war, but at the same time discovered new opportunities in the international market. Integration into European transport networks, the development of multimodal transport and the involvement of innovative technologies will be key factors in ensuring their sustainable development and recovery after the end of the war.
Keywords: development; international transportation; transport; Ukraine; war; problems; obstacles; measures